2011
DOI: 10.1371/journal.pntd.0001378
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Aedes aegypti and Dengue as Influenced by Weather and Human Behavior in San Juan, Puerto Rico

Abstract: Previous studies on the influence of weather on Aedes aegypti dynamics in Puerto Rico suggested that rainfall was a significant driver of immature mosquito populations and dengue incidence, but mostly in the drier areas of the island. We conducted a longitudinal study of Ae. aegypti in two neighborhoods of the metropolitan area of San Juan city, Puerto Rico where rainfall is more uniformly distributed throughout the year. We assessed the impacts of rainfall, temperature, and human activities on the temporal dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
197
1
19

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 234 publications
(237 citation statements)
references
References 43 publications
20
197
1
19
Order By: Relevance
“…Production of Ae. aegypti from urban containers can be instrumental in triggering DENV outbreaks during the dry season (19). In fact, this study found a significant number of houses with tanks holding water for human consumption C.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Production of Ae. aegypti from urban containers can be instrumental in triggering DENV outbreaks during the dry season (19). In fact, this study found a significant number of houses with tanks holding water for human consumption C.…”
Section: Discussionmentioning
confidence: 76%
“…aegypti, across more than 90% of the country (18). Barrera, et al, found that the most important factor determining DENV endemicity was the practice of water storage, which provided a source of mosquito breeding sites (19), especially when the water was not frequently replaced (20). In addition, improvements to water distribution infrastructure have been shown to decrease the incidence of vector-transmitted diseases by decreasing the amount of exposure to infected bites (21).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of rainfall, association delays tend to be shorter, between 1 and 4 weeks (Barrera et al 2011;Scott et al 2000) and it can be argued that changes in adult recruitment by rainfall induced generation of larval habitats could underlie the outbreaks (Chase & Knight 2003;Chaves et al 2012;Yang et al 2009a). In this sense, rainfall and associated changes in relative humidity could ease mosquito dispersal (Edman et al 1998) which maybe essential for population persistence even if local mosquito larval sources are not viable, as suggested by metapopulation persistence of locally inviable populations in models that consider dispersal in autocorrelated environments (Roy et al 2005).…”
Section: Hot Environments and Mosquito Outbreaksmentioning
confidence: 99%
“…Moreover, several long-term studies on Ae. aegypti abundance have shown the abundance of this mosquito species to be correlated with different environmental factors, primarily rainfall and temperature (Barrera et al 2011;Dibo et al 2008;Foo et al 1985;Ho et al 1971;Oo et al 2011;Schultz 1993;Scott et al 2000;Tonn et al 1970), but also with "socio-ecological" factors such as unreliable water supply (Barrera et al 1993;Padmanabha et al 2010) or lack of community engagement in proper water container disposal (Predescu et al 2007). Similar patterns of association between mosquito abundance and weather fluctuations have been observed in other Aedes spp.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution patterns of dengue cases reflect the multifaceted interaction of all these risk factors. The risk of this disease is expected to significantly increase in the near future, and the absence of effective treatment makes the development of adequate vector control strategies more important than ever (Vanwambeke et al, 2007;Barrera et al, 2011).…”
Section: Introductionmentioning
confidence: 99%